Die design and experiments for shaped extrusion under cold and hot condition - Kumar S.; Vijay P. (My University, 2025)
The paper presents designing, fabrication and experiments for shaped extrusion of aluminum alloy (Al 2024) and lead alloy (70Pb30Sn). Flat and conical dies of H, T, L, elliptical and two-hole sections have been designed on the basis of upper bound technique by the authors for cold and hot extrusion. Hot extrusion has been performed in the temperature range 300-500 °C. Experimental investigation have been conducted for average extrusion pressure in cold case for lead alloy (70Pb30Sn) billets and in hot case for commercial grade aluminum (Al 2024) billets respectively. Extrusion pressure in the both cases has been compared with the theoretical work by the author for cold extrusion and for hot extrusion of aluminum alloy, result have been compared with a finite element based commercial package HyperXtrude. Theoretical results obtained by the upper bound technique and the HyperXtrude compares well with the experiments. © 2007 Elsevier B.V. All rights reserved.